Evaluation of the effectiveness of a transfer (interhemispheric) training program in the early stages of fencing training - Witkowski, M.; Bronikowski, M.; Nowik, A.; Tomczak, M.; Strugarek, J.; Kroliczak, G. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: A high level of motor coordination (with an emphasis on the accuracy of hand movements) is an important part of fencers` training. Research on motor coordination shows that both hemispheres of the brain are involved in controlling the action of each of the upper limbs. As the physical training of one hand is believed to significantly increase the performance of the other (untrained) hand, the authors attempt to verify the hypothesis that specialized training of the non-dominant limb can improve the performance of the dominant hand in fencing. METHODS: The study was carried out in Poznan, Poland, in 2015 and involved the experimental (N.=8) and control (N.=8) groups of cadets (12.7±0.5 years old); body mass 38.69±4.08; body height 153.47±6.17), who were randomly selected from fencers belonging to the Fencing Club "Warta" in Poznan, Poland. Participants in the study belonged to one training group with a similar training experience of about 6 years. All participants in the study (N.=16) declared right-handedness during trainings and duels. Their right lateralization was also confirmed in a survey, which was conducted using the Edinburgh Questionnaire. The experimental training program included six weeks of specialized training of the coordination skills of the non-dominant side. It was carried out five times a week. Each session took 30 minutes. The aim of the study was to determine the effect of transfer (interhemispheric) training with the use of the non-dominant hand in particular, on the performance of the dominant hand in fencing. RESULTS: The results indicate that the transfer (interhemispheric) training reduced test accomplishment time in tasks performed with the right upper limb during accuracy tests. The procedures applied in the study also reduced test accomplishment time in tasks performed with the left upper limb. CONCLUSIONS: The study demonstrates that an interhemispheric training program can effectively improve the accuracy of fencing actions, at least in the early stages of training.